Interfacial Zinc Phosphate is the Key to Controlling Biocompatibility of Metallic Zinc Implants - Yingchao Su (Advanced Science, 2019)
Abstract Recently emerged metallic zinc (Zn) is a new generation of promising candidates for bioresorbable medical implants thanks to its essential physiological relevance, mechanical strength, and more matched degradation pace to that of tissue healing. Zn‐based metals exhibit excellent biocompatibility in various animal models. However, direct culture of cells on Zn metals yields surprisingly low viability, indicating high cytotoxicity of Zn. This contradicting phenomenon should result from the different degradation mechanisms between in vitro and in vivo. To solve this puzzle, the roles of all major players, i.e., zinc phosphate (ZnP), zinc oxide (ZnO), zinc hydroxide (Zn(OH)2), pH, and Zn2+, which are involved in the degradation process are examined. Data shows that ZnP, not ZnO or Zn(OH)2, significantly enhances its biocompatibility. The mild pH change during degradation also has no significant impact on cell viability. Collectively, ZnP appears to be the key to controlling the biocompatibility of Zn implants and could be applied as a novel surface coating to improve biocompatibility of different implants.